2013
DOI: 10.1002/uog.13210
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic prediction of vaginal delivery in prolonged labor: a two‐center study

Abstract: Objective To investigate whether head-perineum distance (HPD) measured by transperineal ultrasound is predictive of vaginal delivery and time remaining in labor in nulliparous women OR, 3.11; 95% CI, 3.36; 95% CI, and spontaneous onset of labor (OR, 4.44; 95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 24 publications
4
80
2
4
Order By: Relevance
“…Eggebo et al examine the same parameters on 150 primiparas in the prolonged first stage of labor. They draw the conclusions that both parameters contribute important information about the likelihood of a vaginal delivery and correlate with the time until the completion of delivery [19].…”
Section: Discussionmentioning
confidence: 99%
“…Eggebo et al examine the same parameters on 150 primiparas in the prolonged first stage of labor. They draw the conclusions that both parameters contribute important information about the likelihood of a vaginal delivery and correlate with the time until the completion of delivery [19].…”
Section: Discussionmentioning
confidence: 99%
“…10,13,14 In others studies an AOP of 120° and 110° have been used as a cutoff. 8,12 In present study we found that the cutoff value of 105° was predictive of vaginal delivery, and this range of 15° difference may be due to interobserver variation.…”
Section: Discussionmentioning
confidence: 43%
“…The HPD cutoff value for prediction of vaginal delivery was chosen in accordance with other studies, and the AOP cutoff value was calculated from the predictive value found in this study. 12 The examination was conducted with a Philips VISIQ ultrasound system. The ultrasound transducer was covered with gel and a sterile glove, and pressed firmly to the labia majora when obtaining the measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The angle of progression was describe by Barbera et al 10 who showed that an angle of at least 120° was always associated with subsequent spontaneous vaginal delivery with a good intraand inter-observer variability. Torkildsen et al 11 and Eggebo et al 12 reported that for primiparous women with prolonged first stage of labor, the AOP could predict the probability of a vaginal delivery being the optimal cut-off 110°. Kalache et al 13 reported that for pregnant women in a prolonged second stage of labor, there is a 90% chance of vaginal delivery with an AOP of 120°.…”
Section: Discussionmentioning
confidence: 99%